Predicting the chemical composition of the body and the carcass of 3/4Boer x 1/4Saanen kids using body components - Fernandes, M. H. M. R. [UNESP]; Resende, Kleber Tomás de [UNESP]; Tedeschi, L. O.; Fernandes, J. S. [UNESP]; Teixeira, I. A. M. A. [UNESP]; Carstens, G. E.; Berchielli, Telma Teresinha [UNESP] (Elsevier B.V., 2008)
The determination of the chemical composition of body and carcass is important in nutritional and growth regulation studies. The purpose of this study was to develop equations to predict the chemical composition of body and carcass using chemical composition of body components. Twenty 3/4Boer x 1/4Saanen crossbred male kids, weighing from 20 to 35 kg, were used in this study. The empty body chemical composition was measured by grinding all body components and sampling for chemical analyses. The body components used to estimate body and carcass composition were: neck, fore leg, ribs, loin, hind leg, 9-11 th rib section, non-carcass components (head plus feet, organs plus blood, and hide), visceral fat, and kidney fat. The chemical composition of organs plus blood and 9-11 th rib section had the highest precision to estimate percentage of fat, protein, and water in the body (r(2) of 0.94, 0.82, and 0.90, respectively). For carcass composition, the chemical composition of ribs was the best component to predict all carcass chemical components; however, the equations to estimate the percentages of protein and ash showed a low precision (r(2) = 0.48, 0.44, respectively). The 9-11 th rib section was accurate and precise to estimate carcass fat percentage. We concluded the chemical composition of the body of 3/4Boer x 1/4Saanen crossbred male kids was highly correlated with the composition of body parts, specifically organs plus blood and 9-11 th rib section. Further studies should focus on evaluating these body parts for different breeds and genders under different production scenarios. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: body; Carcass; Composition; components; Goats; prediction